Perspectives of air cargo activities in case of Debrecen International Airport - Virág, László (Acta Agraria Debreceniensis, 2012)
The improvement of Debrecen International Airport has been taking place for more than a decade. The goal is to revitalise the domestic and international aviation of regional centres and connect the Debrecen centred economy zone with other industrial and commercial regions. Considering the market segments of the air cargo industry, and sizing up the requirements of the enterprises, we are seeking to answer for what possibilities an air cargo operation has, and scheduled cargo flights, what alternatives the location of a cargo base has. Getting to know the technical background of ground handling, communication, safety, and security, we can state that the airport is able to handle international cargo aircrafts as well. Regarding to the quantity of frights, we find that there is a possibility of two flights per week. There is minor need of handling dangerous or unique parcels. The surrounding area of working zone is an excellent territory for locating and building cargo facilities, and its technical background. In case of continuously increasing traffic it is suggestible to use the territory behind the apron as a first step of the development. As the activity extends the second step could be the improvement of the southern zone just beside the runway. This way primarily the scheduled air cargo flights could appear, then as the traffic of commercial scheduled flights increases simultaneously could grow the amount of small parcel transportation.